Du coton traditionnel au coton colonial, le coup de force du progrès (Nord-Cameroun) - Christian Seignobos (Revue d'ethnoécologie)
As a country under mandate from the League of Nations, Cameroun first didn’t have to participate in the development of colonial cotton production. The northern part of the country continued to sustain a very lively weaving craft, using an array of local cotton species and perennial cultivations. Witnessing the excesses perpetuated in Tchad along the forced introduction of cotton in the 1930’s, the colonial administration in Cameroun opposed its arrival on its territory. In this regard, it echoed the many suspicions raised by local chiefs and their communities.Nonetheless, against everyone’s judgement, the newly appointed High Commissioner of the French Republic in Cameroun started promoting colonial cotton in 1950, as the only commercial item able to raise North Cameroun out of economic underdevelopment. Its success resided in the creation of a dedicated team of experts, led by the director of the Cfdt, the Compagnie Française pour le Développement des Fibres Textiles (French Company for the Development of Textile Fibres). The inception of colonial cotton production in Cameroun shows the extent of state interventionism and greatly influenced the business model of the African cotton industry, dominated by the ever-powerful Cfdt-Sodecoton.